Does firm value move too much to be justified by subsequent changes in cash flow? - Borja Larrain; Motohiro Yogo (Federal Reserve Bank of Boston, 2005)
Movements in the value of corporate assets are justified by changes in expected future cash flow. The appropriate measure of cash flow for valuing assets is net payout, which is the sum of dividends, interest, and net repurchases of equity and debt. When discount rates are low and equity issuance is high, expected cash-flow growth is low because firms repurchase debt to offset equity issuance. A variance decomposition of the ratio of net payout reveals little transitory variation in discount rates that is not offset by common variation with expected cashflow growth.
Keywords: G12; G32; G35; 330; asset valuation; excess volatility; payout policy; Unternehmenswert; Ertragswert; Cash Flow; USA